The potential for use of non-thermal plasma in microbiology and medicine - Julák, J; Scholtz, V (Epidemiologie, mikrobiologie, imunologie, 2020)
The overview provides basic information on non-thermal plasma, its properties, and methods of its generation. It gives examples of its use in the inactivation of bacteria including biofilms, fungi, and prions. Related applications in human medicine, namely in wound healing, antitumor therapy, dental medicine, and dermatomycosis therapy are also mentioned.
Keywords: lékařství; Fungi; electrical discharges; biofilm; Medicine; dermatomycosis; Bacteria; Microbiology; lidé; Wound Healing; mikrobiologie; Biofilms; microbial inactivation; Humans; wound healing; biofilmy; plazmové plyny; Plasma Gases; hojení ran